2011
DOI: 10.1524/ract.2011.1802
|View full text |Cite
|
Sign up to set email alerts
|

An integrated study of uranyl mineral dissolution processes: etch pit formation, effects of cations in solution, and secondary precipitation

Abstract: Summary.Understanding the mechanism(s) of uraniummineral dissolution is crucial for predictive modeling of U mobility in the subsurface. In order to understand how pH and type of cation in solution may affect dissolution, experiments were performed on mainly single crystals of curite, PbSolutions included: deionized water; aqueous HCl solutions at pH 3.5 and 2; 0.5 mol L −1 Pb(II)-, Ba-, Sr-, Ca-, Mg-, HCl solutions at pH 2; 1.0 mol L −1 Na-and K-HCl solutions at pH 2; and a 0.1 mol L −1 Na 2 CO 3 solution at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 49 publications
1
5
0
Order By: Relevance
“…Uniquely among the reacted samples, analysis of Na-compreignacite showed a significant Ca concentration and a small amount of Mg after reaction, indicating that other exchangeable cations were also incorporated into the interlayer of the mineral structure for charge balance. Other studies have reported the formation of uranyl neoprecipitates on the mineral surface, as observed during the dissolution of becquerelite single crystals in batch, closed systems with ultrapure water (pH 7) for 24 h (Schindler et al, 2006(Schindler et al, , 2011. In the flow-through porous media of our experiments, solutions were undersaturated with respect to uranyl phases, and thus cation exchange appears to be the mechanism of surface alteration of the original compreignacite minerals.…”
Section: Mechanisms Of Dissolution In Low Carbonate Systemssupporting
confidence: 53%
“…Uniquely among the reacted samples, analysis of Na-compreignacite showed a significant Ca concentration and a small amount of Mg after reaction, indicating that other exchangeable cations were also incorporated into the interlayer of the mineral structure for charge balance. Other studies have reported the formation of uranyl neoprecipitates on the mineral surface, as observed during the dissolution of becquerelite single crystals in batch, closed systems with ultrapure water (pH 7) for 24 h (Schindler et al, 2006(Schindler et al, , 2011. In the flow-through porous media of our experiments, solutions were undersaturated with respect to uranyl phases, and thus cation exchange appears to be the mechanism of surface alteration of the original compreignacite minerals.…”
Section: Mechanisms Of Dissolution In Low Carbonate Systemssupporting
confidence: 53%
“…Burns et al . found that etch pit formation in Becquerelite is pH dependent, and that the formation of etch pits encourages dissolution via a step‐wave dissolution mechanism . The etch pit acts as a nucleation site that becomes a constant source of step‐waves, meaning that the overall dissolution stems outwards from the etch pit in waves.…”
Section: Resultsmentioning
confidence: 99%
“…Long-term tests of the stability and durability of SNF exposed to the weathering (air, mineralized solutions and/or increased temperature), as may happen in underground repositories when engineered barriers fail, have been undertaken (Wronkiewicz et al 1992(Wronkiewicz et al , 1996. Numerous studies on natural uraninite as an analogue for SNF (Janeczek et al 1996) were undertaken with the particular interest both in physico-chemical processes that occur during the alteration (e.g., Finch and Ewing 1992;Isobe et al 1992;Pearcy et al 1994;Finch et al 1996;Murakami et al 1997;Schindler and Hawthorne 2004;Schindler and Putnis 2004;Schindler et al 2004a, b, c;Deditius et al 2007aDeditius et al , b, 2008Schindler et al 2011;Forbes et al 2011) and in the formation of supergene phases as the concentrators of the elements of the interest -uranium and possible fission products (such as Pu, Sr, Np) (Burns et al 1997a, b;Burns 1999a;Burns and Hill 2000;Cahill and Burns 2000;Li and Burns 2001;Burns and Li 2002;Burns et al 2004;Klingensmith and Burns 2007;Klingensmith et al 2007). The long-term tests (Wronkiewicz et al 1992(Wronkiewicz et al , 1996 showed that the alteration mechanisms for nuclear fuel and uraninite lead to the same weathering products.…”
Section: Uraninite and Spent Nuclear Fuelmentioning
confidence: 99%